Regulatory Roles of Six-Transmembrane Epithelial Antigen of the Prostate Family Members in the Occurrence and Development of Malignant Tumors - Chen, Wen-Jia; Wu, Hua-Tao; Li, Chun-Lan; Lin, Yi-Ke; Fang, Ze-Xuan; Lin, Wen-Ting; Liu, Jing (Frontiers in Cell and Developmental Biology, 2021)
The human 6-transmembrane epithelial antigen of the prostate (STEAP) proteins, which include STEAP1-4 and atypical STEAP1B, contain six transmembrane domains and are located in the cell membrane. STEAPs are considered archaeal metal oxidoreductases, based on their heme groups and F420H2:NADP+ oxidoreductase (FNO)-like structures, and play an important role in cell metal metabolism. Interestingly, STEAPs not only participate in biological processes, such as molecular transport, cell cycling, immune response and intracellular and extracellular activities, but also are closely related to the occurrence and development of several diseases, especially malignant tumors. Up to now, the expression patterns of STEAPs have been found to be diverse in different types of tumors, with controversial participation in different aspects of malignancy, such as cell proliferation, migration, invasion, apoptosis and therapeutic resistance. It is clinically important to explore the potential roles of STEAPs as new immunotherapeutic targets for the treatment of different malignant tumors. Therefore, this review focuses on the molecular mechanism and function of STEAPs in the occurrence and development of different cancers in order to understand the role of STEAPs in cancer and provide a new theoretical basis for the treatment of diverse cancers.